Development of Contextually Based Mathematics Learning Modules in Improving Numeracy Literacy for Class V Students - Astika Dewi, Made Sri; Nurgiansah, T Heru (CV. Rayyan Dwi Bharata, 2025)
This research is motivated by several issues, namely: the implementation of numeracy literacy learning in grade V elementary school has not been maximized due to the lack of additional teaching materials to support numeracy literacy learning, resulting in grade V elementary school students not being very interested in learning it. This study aims to obtain clear information about: 1) Development of contextual-based mathematics learning modules in improving numeracy literacy of grade V elementary school students; 2) The feasibility of contextual-based mathematics learning modules according to experts; 3) Student responses to contextual-based mathematics learning modules in improving numeracy literacy of grade V elementary school students. This research uses a research and development (RD) method and the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) development model. Data collection methods in this study include: 1) Observation, 2) Questionnaire, 3) Interview. The data analysis technique used is qualitative descriptive statistics. Qualitative data are the result of validation scores from several experts, namely subject matter experts, language experts, and media experts. The results of this development study produce the feasibility of the developed module and student responses to the developed module. The assessment results for this module development obtained feasibility scores from several experts, namely: 1) media experts who obtained a score of 3.30 in the